Corrosion-resistant coatings technology / Ichiro Suzuki - Suzuki, Ichiro (Corrosion technology (New York, N.Y.), 1989)
Helping engineers select and apply widely used metallic, inorganic and organic coatings in natural environments, this authoritative focuses on coatings that protect against moisture, water, pollutants, and aggressive speciues. It closely examines their protective mechanisms, production methods, physical and chemical properties and protective abilities in various environments.